Neuroanatomy for the XXIst Century - Kathleen S. Rockland (Frontiers Research Topics, 2016)
An explosion of new techniques with vastly improved visualization and sensitivity is leading a veritable revolution in modern neuroanatomy. Basic questions related to cell types, input localization, and connectivity are being re-visited and tackled with significantly more accurate and higher resolution experimental approaches. A major goal of this e-Book is thus to highlight in one place the impressive range of available techniques, even as these are fast becoming routine. This is not meant as a technical review, however, but rather will project the technical explosion as indicative of a field now in a vibrant state of renewal. Thus, contributions will be mainly research articles using the newer techniques. A second goal is to showcase what has become the conspicuous interdisciplinary reach of the field: neuroanatomical standards and the close association of structure-function and underlying circuitry mechanisms are increasingly relevant to investigations in development, physiology, and disease. Another feature of this Research Topic is that it includes a breadth of cross-species contributions from investigators working with rodent, nonhuman primate, and human brains. This is important since most of our current knowledge of brain structure has been obtained from experimental animals. However, recent technical advances, coupled with researcher willingness to use the human tissue available, will undoubtedly lead to major advances in the near future regarding human brain mapping and connectomes. Thus, of particular interest will be the methods that can help to define general wiring principles in the brain, both structural and functional. Overall, the state of the field is: exciting.